2015
DOI: 10.1039/c5gc00473j
|View full text |Cite
|
Sign up to set email alerts
|

Commercial process for the recovery of metals from ITO etching industry wastewater by liquid–liquid extraction: simulation, analysis of mechanism, and mathematical model to predict optimum operational conditions

Abstract: A commercial process for the recovery of metals from the indium-tin-oxide (ITO) etching industry wastewater by liquid-liquid extraction has been developed. A suitable cross current simulated batch process was developed, and extraction mechanisms involved in the process were analyzed. Mathematical models were proposed to correlate metal extractability with respect to extractant concentrations and metal loading with respect to the solvent/solution volume ratio. Optimum conditions required for the complete scrubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The purpose of the current investigation is to determine the missing link between the LCD dismantling process developed for metal beneficiation and the recovery of indium from LCD glass via the hydrometallurgy route [7,8,33]. Elsewhere our reported process indicates that dismantling of waste to LCD glass, leaching of indium followed by indium recovery from LCD waste has already been developed [7,8,33]. However, an important drawback of these studies is that whether size has a predominant effect on leaching efficiency has not been reported, which could be a determining factor for industrial valorization of waste LCD glass [33].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the current investigation is to determine the missing link between the LCD dismantling process developed for metal beneficiation and the recovery of indium from LCD glass via the hydrometallurgy route [7,8,33]. Elsewhere our reported process indicates that dismantling of waste to LCD glass, leaching of indium followed by indium recovery from LCD waste has already been developed [7,8,33]. However, an important drawback of these studies is that whether size has a predominant effect on leaching efficiency has not been reported, which could be a determining factor for industrial valorization of waste LCD glass [33].…”
Section: Introductionmentioning
confidence: 99%
“…21 IGZO, a better semiconducting material, which was considered to be the most promising thin-lm transistor for the next generation at panel displays, has shown great potential for replacing ITO. 22,23 At present, there are mainly ve methods to separate and recycle indium from spent ITO targets: vacuum-chlorinated separation, 24,25 vacuum carbonization reduction, 26 solvent extraction separation, [27][28][29] ion-exchange, 30,31 and biological metallurgy separation. 32 In our previous study, HCl gas was utilized to react with In 2 O 3 and SnO 2 at 373 K for 60 min to obtain InCl 3 and SnCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…99 wt% of indium was recovered with a purity around 90%. Swain et al 28 reported a recovery rate of 97.78% for Sn with 99% purity by using the extractant cyanex 272.28 LópezDíaz-Pavón et al 31 utilized the cationic ionexchange resin Lewatit K-2621 to separate indium from tin. Higashi et al 32 recovered indium by adding the Shewanella algae into the leached solution to concentrate the indium for 680 times.…”
Section: Introductionmentioning
confidence: 99%
“…Indium consumption has increased very rapidly over the past 10 decade because it is essential element in ITO (indium tin oxide), 11 which is mainly used for manufacturing of flat panel displays, 12 touch panels, transparent electrode and solar cells etc. Although it 13 is expected to deplete of the earth's reserves within 20 years, the 14 demand and consumption of indium is rising every year 15 [1,2].…”
mentioning
confidence: 99%
“…Therefore, development of the efficient recovery process is 16 extremely important for stable supply of indium in along with the 17 issue of resource recycle and environmental sustainability [3][4][5][6][7][8][9]. 18 Conventional methods for the indium recovery from secondary 19 resource as industrial wastewater include precipitation [10], 20 solvent extraction [11][12][13] and adsorption method [14][15][16][17][18][19][20][21][22]. The 21 precipitation and solvent extraction is well-known recovery 22 method, but they generate the potential environmental problems 23 cause by the use of large amount of chemicals and organic solvents 24 [23][24][25][26][27].…”
mentioning
confidence: 99%